2009
DOI: 10.2118/113460-pa
|View full text |Cite
|
Sign up to set email alerts
|

A New Polymer Application for North Sea Reservoirs

Abstract: Summary Field trials have demonstrated increased oil recovery by injection of colloidal dispersion gels (CDG). Characteristics of these trials include reservoirs characterized by high permeability heterogeneity and low injection water salinities. The enhanced oil recovery (EOR) has been attributed to improved waterflood sweep in the rather heterogeneous reservoirs where this method has been applied. This study presents an investigation of the applicability of CDG at higher salinity, and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 24 publications
3
55
0
Order By: Relevance
“…In order to mobilize the capillary trapped oil, the capillary forces must decrease or viscous forces increase. The microscopic flow diversion caused by the log-jamming mechanism has been identified to play a dominant role on recovering the capillary trapped oil during the injection of LPS (Spildo et al 2008). The LPS entrapment mechanisms change the local force balance that, in turn, can lead to the oil mobilization.…”
Section: Coupled Quasi Static Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to mobilize the capillary trapped oil, the capillary forces must decrease or viscous forces increase. The microscopic flow diversion caused by the log-jamming mechanism has been identified to play a dominant role on recovering the capillary trapped oil during the injection of LPS (Spildo et al 2008). The LPS entrapment mechanisms change the local force balance that, in turn, can lead to the oil mobilization.…”
Section: Coupled Quasi Static Modelmentioning
confidence: 99%
“…More recently, there have been several reports of CDG field trials (Chang et al 2006;Dias et al 2008) where also incremental oil recovery was observed. The conventional approach from the 1980's target mainly macroscopic sweep improvement, while the more recent CDG approach also named Linked Polymer Solution (LPS) discussed in Aarra et al (2005), Bjørsvik et al (2007), Bjørsvik (2008), and Spildo et al (2008) aim at improving the microscopic displacement efficiency in addition to the macroscopic sweep.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding BrightWater® [108], at the present time Milne Point in Alaska is the only field application discussed or documented in the public domain [109,110]. However, it is expected that the number of CDG's and BrightWater® field applications will increase in the near future based on recent field and laboratory studies underway, opening a new window of opportunities for EOR chemical methods [111][112][113][114].…”
Section: Chemical Methodsmentioning
confidence: 99%
“… Polymer flooding has gained recent interest for offshore EOR applications including the injection of Colloidal Dispersion Gels or CDG [18,27,114]. Some examples of proposed or field polymer flood test include:…”
Section: Eor Offshorementioning
confidence: 99%
“…Polymer flooding is recently gaining interest for viscous oil reservoirs (Wassmuth et al 2009) and offshore fields (Spildo et al 2009). Chemical EOR technology is dramatically evolving better than 30 years ago due to more experiences, better understanding, better modeling, and better chemicals at lower cost (Alvarado et al 2011;Koning et al 1988;Li et al 2003;Manrique et al 2000;Meyers et al 1992;Vargo et al 2000).…”
Section: Introductionmentioning
confidence: 99%